PENGARUH JUMLAH POROGEN PADA SINTESIS MIP (MOLECULARLY IMPRINTED POLYMER) TERHADAP ADSORPSI MIP-KLORAMFENIKOL - Maria Monica Sianita; Trifena Meysia Yusuf (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2022)
The purpose of this study was to determine the effect of porogen acetonitrile volume during the synthesis of Molecularly Imprinted Polymer (MIP) toward the adsorption capability of chloramphenicol and to determine the characteristics of the functional groups contained in Non Imprinted Polymer (NIP) and MIP. The porogen variations used were 30 mL, 45 mL, dan 60 mL. The effect of volume of porogen to adsorption capability will be measured using High Performance Liquid Chromatography (HPLC) instruments, while the functional groups on NIP and MIP will be characterized using Fourier Transform Infra Red (FTIR). MIP was synthesized using the precipitation method. The results showed that the 60 mL of the porogen variation gave the highest adsorption capability value compared to other variation which was 7.32 mg/g. Characterization with FTIR showed that the presence of NO2 group in NIP which was indicated at wave number 1517.56 cm-1 and 1549,08 cm-1 while in MIP the NO2 group was detected at wave number 1553.07 cm-1 with lower intensity. Key words: MIP, chloramphenicol, acetonitrile, adsorption capability.